2022
DOI: 10.1002/pen.25926
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–structure‐interaction simulations of forming‐air impact thermoforming

Abstract: The authors present a thermally and dynamically coupled fluid–structure‐interaction (FSI) model of a thermoforming process variant along with simulation results. By purposeful arrangement of the inlet nozzles, the process variant under consideration seeks to improve the deformation behavior of a plastic sheet made of polyvinyl chloride (PVC), ultimately leading to a more uniform wall thickness distribution. In order to capture the complex interaction between deforming sheet and turbulent flow field in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Thus, it would be possible to direct more force vectors towards the sidewalls of materials to enable better forming. The performance of such a configuration has already been tested in laboratory studies on plastic thermoforming, as shown in Figure 11 35,36 . The studies described used directional pressure for optimising the thickness distribution of plastic samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it would be possible to direct more force vectors towards the sidewalls of materials to enable better forming. The performance of such a configuration has already been tested in laboratory studies on plastic thermoforming, as shown in Figure 11 35,36 . The studies described used directional pressure for optimising the thickness distribution of plastic samples.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of such a configuration has already been tested in laboratory studies on plastic thermoforming, as shown in Figure 11. 35,36 The studies described used directional pressure for optimising the thickness distribution of plastic samples. Nevertheless, fibre-based materials can also benefit from further research on such systems.…”
Section: Effect Of Forming Operation and Tooling On Shape Accuracymentioning
confidence: 99%
“…Both induce more favorable thickness gradients (Ayadi et al 2020;Duarte and Covas 2008;Martin and Duncan 2007;Marathe et al 2016;McCool and Martin 2010;Sasimowski 2017). Recently, Wagner et al (2022), applied controlled pressure forming to improve the thickness distribution of a cup using a female mold.…”
Section: Introductionmentioning
confidence: 99%